Natural Trap Cave tephra correlation to Yellowstone using U-series (230Th/238U) dates and oxygen isotopes of zircon and chemical composition of adherent glass - Schmitt, Axel Karl; Clementz, Mark T.; Lovelace, David M.; Chamberlain, Kevin R. (Quaternary international, 2023)
Zircon crystals from ash layers intercalated with fossil-rich sediment from Natural Trap Cave (NTC) in Wyoming (USA) were investigated to refine the chronostratigraphy of this unique late-Quaternary megafaunal assemblage. Glass compositions of individual glass spicules and glass adherent to zircon along with a characteristic low-δ18O signature of zircon (on average + 2.4‰ relative to Vienna standard mean ocean water) indicate tephra provenance from post-Lava Creek Tuff activity of Yellowstone. Yellowstone glass composition was hence used to anchor the 230Th/238U zircon isochron and to compute model crystallization ages, which translate into maximum depositional ages. For the lowermost visible tephra layer in new excavations in NTC strata, an upper age limit of 138 ± 9 ka (1σ age uncertainty) was thus obtained. A younger tephra with a230Th/238U zircon date of 111 ± 8 ka is tentatively correlated with Tuff of Cold Mountain Creek from the Central Plateau Member of Yellowstone, suggesting a minor lag time between zircon crystallization and eruption. The NTC tephra record thus has high potential for refining the explosive volcanic history and tephra distribution patterns of Yellowstone during the late Pleistocene.
Online verfügbar 21. Februar 2022, Artikelversion 28. Januar 2023
Im Titel sind die Zahlen 230 und 238 hochgestellt
Gesehen am 26.05.2023